2021
DOI: 10.1177/10556656211015007
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Hospital Characteristics on Mandibular Distraction Osteogenesis Outcomes Among Patients With Pierre Robin Sequence Utilizing a National Inpatient Database

Abstract: Objectives: This study collected national inpatient data to investigate the impact of hospital specialty and size on patient outcomes following mandibular distraction osteogenesis (MDO). Design: Kids’ Inpatient Database was used to identify patients less than 12 months of age with Pierre Robin sequence (PRS) who underwent MDO in one of the following years: 2006, 2009, and 2012. Setting: Inpatient database from the United States. Participants: Two hundred seventy-six patients with PRS underwent MDO with 134 (48… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…This population-based cohort study reported on survival and hospitalisations of 463 children born with PRS in nine European countries, which is in contrast to many of the published studies on PRS limited to case series 19. We were not able to analyse data separately for children with isolated PRS and those with associated anomalies.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…This population-based cohort study reported on survival and hospitalisations of 463 children born with PRS in nine European countries, which is in contrast to many of the published studies on PRS limited to case series 19. We were not able to analyse data separately for children with isolated PRS and those with associated anomalies.…”
Section: Discussionmentioning
confidence: 91%
“…This population-based cohort study reported on survival and hospitalisations of 463 children born with PRS in nine European countries, which is in contrast to many of the published studies on PRS limited to case series. 19 We were not able to analyse data separately for children with isolated PRS and those with associated anomalies. However, an estimated 72% of children were likely to have had isolated PRS, as observed in a recent EUROCAT study on the epidemiology of PRS which included most of the children in this study.…”
Section: Discussionmentioning
confidence: 99%